2005
DOI: 10.1103/physrevd.71.105006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiplicative noise in relativistic phase transitions

Abstract: Effective stochastic equations for the continuous transitions of relativistic quantum fields inevitably contain multiplicative noise. We examine the effect of such noise in a numerical simulation of a temperature quench in a 1+1 dimensional scalar theory. We look at out-of-equilibrium defect formation and compare our results with those of stochastic equations with purely additive noise.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Starting with the high-dissipation results with α = 1.0, we see that within error-bars, the scaling exponent is approximately constant for β < 0.5. The value measured σ = 0.28, coincides with that obtained for similar simulation parameters in the case of a single field system [48]. One should note that the method used to determine the final defect density is known to lead to a slight over-estimate in σ when compared to other, computationally more demanding, approaches (for a discussion see [12]).…”
Section: Numerical Simulations Of Defect Formationsupporting
confidence: 78%
See 1 more Smart Citation
“…Starting with the high-dissipation results with α = 1.0, we see that within error-bars, the scaling exponent is approximately constant for β < 0.5. The value measured σ = 0.28, coincides with that obtained for similar simulation parameters in the case of a single field system [48]. One should note that the method used to determine the final defect density is known to lead to a slight over-estimate in σ when compared to other, computationally more demanding, approaches (for a discussion see [12]).…”
Section: Numerical Simulations Of Defect Formationsupporting
confidence: 78%
“…The relation between these two terms ensures that the fluctuation-dissipation theorem is satisfied and guarantees that for very large times thermal equilibrium at temperature Γ/2 is reached. A simpler version of this model with one single field has been used successfully in several studies of defect formation in 1+1 dimensions [12,48]; we refer the reader to these for more a detailed discussion of the model and its numerical implementation.…”
Section: Numerical Simulations Of Defect Formationmentioning
confidence: 99%
“…The existence of these additional terms in the GLL equation will, of course, play an important role in the dynamics of the formation of condensates. For instance, it was shown that the effects of multiplicative noise are rather significant in the Kibble-Zurek scenario of defect formation in one spatial dimension [18]. Although in the literature there are many different approaches for studying the nonequilibrium dynamics in field theory [19,20,21], the use of stochastic Langevin-like equations of motion is still a simpler and more direct approach in many different contexts in statistical physics and field theory in general.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these additional terms in the GLL equation will, of course, play an important role in the dynamics of the formation of condensates. For instance, it was shown that the effects of multiplicative noise are rather significant in the Kibble-Zurek scenario of defect formation in one spatial dimension [18].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect of the new contributions on the relevant time scales for phase ordering, we consider a scalar λ φ 4 theory in the broken phase. It was shown recently that the effects of multiplicative noise are rather significant in the Kibble-Zurek scenario of defect formation in one spatial dimension [14]. We perform (3 + 1)-dimensional real-time lattice simulations to study the behavior of the inhomogeneous scalar field, taking into account lattice counter-terms that guarantee lattice-size independence [15,16,17].…”
mentioning
confidence: 99%